2006
DOI: 10.1007/s10439-006-9132-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards A Noninvasive Method for Determination of Patient-Specific Wall Strength Distribution in Abdominal Aortic Aneurysms

Abstract: The spatial distributions of both wall stress and wall strength are required to accurately evaluate the rupture potential for an individual abdominal aortic aneurysm (AAA). The purpose of this study was to develop a statistical model to non-invasively estimate the distribution of AAA wall strength. Seven parameters--namely age, gender, family history of AAA, smoking status, AAA size, local diameter, and local intraluminal thrombus (ILT) thickness--were either directly measured or recorded from the patients hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
180
1
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(191 citation statements)
references
References 37 publications
1
180
1
9
Order By: Relevance
“…The latter involves information that is not readily available, but can be indirectly estimated by factoring in biomechanical and clinical parameters, as well as the medical history of the specific patient. The RPI 55 that was incorporated in our methodology is a first step toward achieving such an estimate. The strength mapping that we have conducted clearly indicated that wall strength was significantly reduced at the aneurysmal bulge, compromising the integrity of the aortic wall (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter involves information that is not readily available, but can be indirectly estimated by factoring in biomechanical and clinical parameters, as well as the medical history of the specific patient. The RPI 55 that was incorporated in our methodology is a first step toward achieving such an estimate. The strength mapping that we have conducted clearly indicated that wall strength was significantly reduced at the aneurysmal bulge, compromising the integrity of the aortic wall (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…55 There is a significant reduction in AAAs wall tensile strength as compared to non-aneurysmal tissue. 40 Recent ex-vivo studies of AAA biomechanical properties focused on the extracellular matrix structure and basic properties related to wall stiffness.…”
Section: Biomechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the intraluminal thrombus (ILT) thickness, sex, family history, and smoking on the AAA strength have been well examined in computational models of AAAs [3,50]. In addition, Di Martino et al [51] suggested a weak (but significant) negative correlation (R ¼ À0.42 and P ¼ 0.012) between the AAA wall thickness and its tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the inclusion of bending stiffness in our analysis intensifies the effects of spine contact on the morphology, wall stress distribution, and PWS, beyond what we observed in this study. Accurate measures of wall strength are yet to be considered in our analysis for a reliable assessment of rupture [50,51,57,58]. Our simulation cases represent hypothetical models of AAAs initiated by artificial elastin degradation in a healthy aorta instead of the real elastin loss in a patient's AAA wall.…”
Section: Discussionmentioning
confidence: 99%